Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers

Synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an important intermediate for (3S,4R)-Cisapride - Shirode, Nilesh M.; Likhite, Anjali P.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2008)
An efficient synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an useful intermediate for the chiral synthesis of important drug molecule Cisapride and its analogs, from enantiopure 4-formylazetidin-2-one is described. Synthesis of trans as well as cis isomers of 4-amino-3-methoxypiperidine from 4-formylazetidin-2-one is also achieved in good yield. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: 4-aminopiperidine; azetidin-2-ones; Cisapride; Staudinger reaction; stereoselective synthesis

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Facile synthesis of N-substituted maleimides - Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Chaudhary, Preeti M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
A simple and efficient method for the synthesis of N-substituted malemides from the corresponding maleamie acids under the phase transfer catalysis has been described
Keywords: Maleamic acids; maleimides; phase transfer catalysis; synthesis

First regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles - Rode, Navnath D.; Sonawane, Amol D.; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P. (Tetrahedron Letters, 2015)
The regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles is described for the first time. The iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles using molecular iodine afforded diiodo-compound which on Cul-catalyzed intramolecular C-N coupling reaction gave six-membered 2-aryl-51141,2,4]triazolo[5,1-b][1,3]thiazines, whereas, the five membered 3-aryl-5,6-dihydrothiazolo[2,3-c][1,2,4]triazoles were obtained exclusively when the iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles was carried out using NIS. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iodocyclization; Regloselective; Thiazine; Triazole

Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis